Blood pressure variability combined with coagulation function in early prediction and outcome assessment of germinal matrix-intraventricular hemorrhage in preterm infants with gestational age ≤32 weeks. - Lijun Jiang; Qian Yu; Hui Li; Fudong Wang; Feng Liu; Zhenxing Xu (PLoS ONE, 2025)
Objective To determine the association between blood pressure variability (BPV), coagulation indexes, and germinal matrix-intraventricular hemorrhage (GMH-IVH) in preterm infants with gestational age ≤ 32 weeks. In addition, we aimed to determine whether the combination can predict the occurrence and outcome of GMH-IVH. Methods This retrospective study included 106 preterm infants. According to the presence of GMH-IVH, the preterm infants were divided into GMH-IVH (51 patients) and no GMH-IVH (55 patients) groups. Furthermore, according to the short-term prognoses, the GMH-IVH group was subdivided into good outcome (30 patients) and poor outcome (21 patients) groups. Coagulation function and BPV indexes were collected at admission. Univariate analysis, logistic regression model, and receiver operating characteristic curve were used to analyze the relationship between indexes and the occurrence and outcome of GMH-IVH in preterm infants. Results Univariate analysis showed that the difference between maximum and minimum (Max-Min); standard deviation (SD); coefficient of variation (CV) of BPV, prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (APTT), and proportion of premature rupture of membranes (PROM) were higher in the GMH-IVH group than the no GMH-IVH group (P < 0.05). Logistic regression analysis showed that INR and DBP SD were directly correlated with GMH-IVH, and the joint curve had the largest area under the curve (AUC) (82.4% sensitivity and 79.7% specificity). BPV SD, BPV CV, APTT, and INR were higher in the poor outcome group than in the good outcome group (P < 0.05). Logistic regression analysis showed that INR and DBP SD were directly correlated with poor outcomes in preterm infants with GMH-IVH. The joint curve had the largest AUC (sensitivity 76.2% and specificity 90.0%). Conclusion Increased INR and DBP SD are directly associated factors for the developement and poor short-term outcome of GMH-IVH, and combined monitoring of INR and DBP SD has certain reference value for the early identification and prognosis evaluation of GMH-IVH in preterm infants with gestational age ≤ 32 weeks.